Avaliação da expressão gênica das ciclooxigenases 1 e 2 em modelo clinico de analgesia preemptiva sob uso de diferentes antiinflamatórios não esteroidais em cirurgias para remoção de terceiros molares mandibulares - Albuquerque, Assis Filipe Medeiros (2018)
Cyclooxygenases (COXs) play an important role in the development of inflammatory events related to third molar surgeries. Although the preoperative use of nonsteroidal antiinflammatory drugs (NSAIDs) has been considered in such procedures, studies correlating the gene expression of COXs are scarce. In this context, the present thesis is composed by two chapters that aim, respectively: 1) to carry out a systematic review on the gene expression in surgeries of third molars; 2) to evaluate the gene expression of COXs 1 and 2 in an oral model of preemptive analgesia under the use of different NSAIDs. In Chapter 1, a systematic review registered on the PROSPERO platform under number 42017060455 was carried out according to the recommendations of the PRISMA guide. The results of this study showed the variability of methodologies about the type of material collected, medications used and genes evaluated, which makes it difficult to obtain consistent data on the relationship between the actual clinical efficacy of the medications and the expression of COX isoforms. In Chapter 2, a randomized, double-blind, placebo-controlled clinical trial was conducted to evaluate the effect of two NSAIDs and their relationship with COXs 1 and 2 gene expression in an oral model of preemptive analgesia involving the surgical removal of mandibular third molars. Eligible patients were those who needed to perform the removal of the two lower third molars with similar inclusion pattern, being between 18 and 35 years old. They were randomly allocated into three groups to receive 1 hour before the procedure a single dose of ibuprofen 400mg, etoricoxib 120mg or placebo. A sample of gingival tissue was obtained shortly after anesthesia and 30 minutes after the beginning of the surgical procedure to evaluate the temporal course of mRNA expression for the COXs by quantitative real-time polymerase chain reaction (qRT-PCR). All groups had a significant decrease in COX-2:COX-1 from T0 to T30 (placebo, p=0.013, ibuprofen, p<0.001, etoricoxib, p=0.047). Experimental groups showed a significant correlation between COX-1 and COX-2 levels and clinical pain parameters, and the ibuprofen group showed an opposite correlation between COX-1 expression and maximum mouth opening (p <0,05). In conclusion, induction of COX-2 mRNA was directly related to tissue inflammation triggered in third molar surgeries, as well as the relationship between COX-1 and COX-2 levels was inversely proportional to preoperative NSAID selectivity, which corroborated with the clinical findings of pain found.